2018
DOI: 10.1177/1534735418808597
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Unmet Information Needs: Results of a Clinician-Led Consultation Service About Complementary and Alternative Medicine for Cancer Patients and Their Relatives

Abstract: Purpose. To report on a telephone consultation service with cancer patients and their relatives about complementary and alternative medicine (CAM) between 1999 and 2011. Methods. We offered a Germany-wide, free-of-charge telephone consultation service about CAM led by oncology clinicians from a comprehensive cancer center. The consultations followed a patient-centered approach with the aim to provide guidance and evidence-based information. Sociodemographic, disease-related data as well as information about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…This difference may be explained by higher CAM use amongst women and higher information seeking activity amongst breast cancer survivors [45e47]. It is important that HCPs communicate openly with cancer survivors about CAM in order to identify potentially harmful practices while supporting survivors' holistic goals [48,49]. This may increase self-efficacy, internalise locus of control and improve the sense of wellbeing associated with feeling like a participant in one's own recovery [26,48,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be explained by higher CAM use amongst women and higher information seeking activity amongst breast cancer survivors [45e47]. It is important that HCPs communicate openly with cancer survivors about CAM in order to identify potentially harmful practices while supporting survivors' holistic goals [48,49]. This may increase self-efficacy, internalise locus of control and improve the sense of wellbeing associated with feeling like a participant in one's own recovery [26,48,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 53 of 57 allocated to IOD-CAM completed the intervention and we consider it feasible to integrate in standard oncology care. The high completion rate could be an expression of patients' substantial need for reliable information and counselling about CAM as an integrated part of oncology care [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…We advanced the findings of a previous project [10] into a communication manual for a multicenter physician-led consultation service and implemented and evaluated the service at 7 cancer centres. Based on the manual, we developed a training programme for gynaecologists consulting cancer patients about CAM and tested the programme in a pilot randomized study [17].…”
Section: Evaluation Of Physician-led Consultation Servicesmentioning
confidence: 99%
“…Findings from a clinician-led consultation service about CAM, funded by the German Cancer Aid since 1999, showed that a guideline-oriented, patient-centred approach provides physicians with the opportunity to engage in open and supportive dialogues about CAM to help with symptom management, psychological support, and individual self-care [10].…”
Section: Introductionmentioning
confidence: 99%